The Finnish banking crisis and its handling - Peter Nyberg; Vesa Vihriälä (Bank of Finland, 1993)
The paper gives a brief description of the evolution of the Finnish banking crisis and its handling. 1n the first section, the salient features of the Finnish banking system are described. We then briefly discuss the liberalization process, macroeconomic and regulatory policies, and the subsequent credit boom and its development into a recession of unprecedented depth. Next, we document the impact on bank profitablity of the drastic changes in macroeconomic conditions. The collapse and rescue of Skopbank are summarized. 1n section 2 we describe the public safety net, starting with the pre-crisis arrangements. This is followed by an exposition of the new measures taken in 1992, with the emphasis on the establishment of the Government Guarantee Fund, its organization, powers and principles of operation. Section 3 gives an account of the support measures taken by the Goverment Guarantee Fund in the course of 1992 and in earIy 1993. Section 4 describes the reform of the bank support arrangements in the earIy months of 1993. Finally, in section 5, we discuss the banks' current economic environment and their prospects in the near future. We also take up some of the major issues of principle relating to the rationalization of the banking sector.
URN:NBN:fi:bof-201808011834
Keywords: 330